Laminação a quente de produtos longos microligados - Roney Eduardo Lino (2018)
The goal of this thesis is to study hot rolling of microalloyed long products. Three chemical compositions were used for this purpose: a CMn alloy, used as a reference alloy, a V microalloyed alloy, traditionally used in the rolling of longs and a NbV alloy where Nb partially substituted V in this traditional alloy for. The main hypotheses concerning this thesis are: a) how Nb added to the traditional V microalloyed alloy will influence the product in terms of hot rolled microestrutures and mechanical properties? b) How would this same Nb affect the process of hot deformation in terms of softening mechanisms, mean flow stresses and phase transformation kinetics? c) Would it be interesting to roll this proposed NbV alloy considering the traditional V alloy used from the viewpoint of cost, operational performance and other industry factors still to be assessed during this work? The procedure adopted here, to answer these questions was to approximate from the real industry line via first mechanical testing in the lab and then mathematical modelling. Industry trials are expensive and, as an experimental method, prone to inherent imprecisions. Hence, dilatometry and torsion experiments were performed first, in preparation for industry trials. Dilatometry was initially performed to verify possible influences of Nb on hardenability when compared to the traditional V alloy and to obtain CCT curves. Torsion experiments were then performed to obtain information on softening mechanisms and means flow stresses. Finally, a mathematical model was developed to predict microstructural evolution and mechanical properties. Industry trials were then designed and run. Results indicated that full softening occurred between most passes, caused by static and/or metadynamic recrystallization. The model indicated possible precipitation of strain induced VN and NbCN in the last rolling passes. The model also indicated possibility that a considerable amount of microalloying elements could be in solid solution during transformation and potentially be used to increase strength via precipitation in ferrite. In general, Nb improved homogeneity of microstructure and increased hardenability of the alloy.